2018
DOI: 10.1101/241513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using insects to detect, monitor and predict the distribution ofXylella fastidiosa:a case study in Corsica

Abstract: 11We sampled ca 2500 specimens of Philaenus spumarius throughout Corsica without a priori 12 on the presence of symptoms on plants. We screened 448 specimens for the presence of 13Xylella fastidiosa (Xf) using qPCR and a custom nested PCR. qPCR appeared versatile and 14 under-estimated the prevalence of Xf. Nested PCR showed that Xf was present in all 15 populations. Molecular results were validated by prediction on the distribution of Xf made 16 from tests conducted on plants, which shows the pertinence of us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…Balearic Islands, lowlands of Corsica island, south-eastern France and the Apulia region). This suggests that risk maps provided in the present study are reliable for the design of surveys, including ‘spy insects’ survey 68,69 . They may also be helpful to anticipate the spread of the different subspecies and provide guidance on which areas should be targeted for an analysis of local communities of potential vectors and host plants to design management strategies and research projects.…”
Section: Discussionsupporting
confidence: 53%
“…Balearic Islands, lowlands of Corsica island, south-eastern France and the Apulia region). This suggests that risk maps provided in the present study are reliable for the design of surveys, including ‘spy insects’ survey 68,69 . They may also be helpful to anticipate the spread of the different subspecies and provide guidance on which areas should be targeted for an analysis of local communities of potential vectors and host plants to design management strategies and research projects.…”
Section: Discussionsupporting
confidence: 53%
“…11%), and insect vectors tend to be frequent around this host (recent molecular analyses have shown that X. fastidiosa is present in c . 20% of insect vectors Philaenus spumarius collected from several C. monspeliensis populations across Corsica; Cruaud et al ., ). However, this host species has been weakly surveyed (3% of samples) in comparison with much less abundant host species, such as Polygala myrtifolia (12% of samples), which is an ornamental plant with an observed infection rate of 26%.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, an analysis of the demography and disease prevalence for a host such as Cistus monspeliensis suggests that it could be, among others, an important component of the hidden compartment. Indeed, C. monspeliensis is very abundant in Corsica (http://www.telabotanica.org), in particular in wild areas; its observed infection rate is quite high (c. 11%), and insect vectors tend to be frequent around this host (recent molecular analyses have shown that X. fastidiosa is present in c. 20% of insect vectors Philaenus spumarius collected from several C. monspeliensis populations across Corsica; Cruaud et al, 2018). However, this host species has been weakly surveyed (3% of samples) in comparison with much less abundant host species, such as Polygala myrtifolia (12% of samples), which is an ornamental plant with an observed infection rate of 26%.…”
Section: New Phytologistmentioning
confidence: 99%
“…Extreme cases include some years after the infection. 22% production in Spain is intensive (Fernandez Escobar et al., ) Control of weeds is a crucial aspect in limiting vector population densities. Vectors and environment have a crucial role in symptoms expression. The vector is wherever olive production is (e.g. Cruaud et al., ). Adults appear in May, are present in orchards from May to September‐October with a population peak in late‐May or June. In some areas of EU (Spain, Greece) vectors are not found in olive orchards during summer.…”
Section: Appendix E – Factsheet and Report Of The Expert Knowledge Elmentioning
confidence: 99%